NGAASIN SEBAGAI PENDIDIKAN KARAKTER: KAJIAN ETNOPEDAGOGI - I Nengah Adi Widana; Ni Made Ari Dwijayanthi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Nowadays, various studies on ethnopedadogies or education in local wisdom are often carried out, the results of which are used to improve the character possessed by students. The cultivation of this character value is relatively more felt because it is based on an existing local wisdom, and occurs in the community. One form of tradition that contains the value of character education is the ngaasin tradition carried out by Pakraman Bukih Village, Belancan Village, Kintamani, Bangli. As one of the traditions that is still carried out and carried out by the community, precisely every last night before the panyineban event, of course it contains character education values that can be utilized in improving the quality of education today. To solve problems and examine the value of character education contained in this tradition, two theories are used, namely semiotic theory and ethnopedagogy. Meanwhile, the method used in this study is a qualitative method with descriptive analysis (qualitative descriptive). Character education contained in the ngaasin tradition carried out by Pakraman Bukih Village, namely: a) awareness of Ida Sang Hyang Widhi Wasa/God Almighty (Spritual), b) fostering social attitudes, c) fostering a sense of togetherness and unity, d) create a sense of independence, e) improve discipline, and f) teach a sense of justice from an early age.Keywords: ngaasin, character education, ethnopedagogy